Preparation and characterization of radiopaque natural rubber - Nisha V S; Joseph Rani (Rubber Chemistry and Technology, 2006)
Currently radiopaque polymers are of great interest to medicine and dentistry because of their wide area of applications such as catheters, surgical tools, dental products, radiation shielders etc. Lead has historically been used as the shielding material, but not without health and environmental concerns. In this work, we have prepared radiopaque materials from natural rubber (NR) through different routes. Natural rubber was iodinated and characterized using UV-VIS spectroscopy, thermo gravimetric analysis and clinical X-ray techniques. The physical properties of Iodinated NR compounds prepared at ambient and high temperatures were studied. The low temperature cured samples showed better radiopacity and conductivity than high temperature cured samples. Radiopaque NR was prepared using radiopacifiers like barytes sulphate, zinc oxide and active zinc oxide. The physical properties of NR vulcanizates with different radiopacifers were studied. Clinical X-ray techniques have been used to confirm the radiopacity. The optical density of the samples were measured and compared with that of conventionally used lead shield.
Keywords: Radiopaque natural rubber